2002
DOI: 10.1136/jnnp.72.6.737
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI findings and cognitive impairment among community dwelling elderly subjects

Abstract: Objectives: To study the factors which influence cognitive impairment among elderly subjects living in a local community, based on both MRI and clinical findings, to further elucidate the causes of dementia, and also to help develop strategies for its prevention. Methods: Cranial MRI and other medical examinations were performed on non-demented elderly subjects who resided in one rural community. A total of 254 subjects aged from 60 to 91 years of age, with a mean age of 73.9 (SD 6.8) were examined. The mini m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…Much more attention has focused on white matter lesions in aging, which was not the focus here. White matter lesions as well as atrophy are associated with cognitive decline in old age [11]. The functional implications of the white matter volume loss reported here, requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Much more attention has focused on white matter lesions in aging, which was not the focus here. White matter lesions as well as atrophy are associated with cognitive decline in old age [11]. The functional implications of the white matter volume loss reported here, requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a previous Japanese population-based study in which most subjects were 470 years old demonstrated the effect of cerebral atrophy on cognitive impairment using the same imaging methodology. 17 This study had several limitations. First, there might have been selection bias.…”
Section: Resultsmentioning
confidence: 99%
“…Using a computer-assisted processing system (Image J version 1.41; National Institutes of Health, Bethesda, MD, USA) and the methods of Koga et al, 17 the percentage cerebrum value (%Cerebrum atrophy) was calculated as an index of cerebral atrophy (Figure 1). First, skull stripping of a T2WI of digital imaging and communication in medicine, involving two slices above the pineal body, was performed.…”
Section: Mrimentioning
confidence: 99%
“…3,4 The possible correlation of LA with cognitive decline or motor deficit has been investigated using visual or computerized methods to assess the LA extent. [5][6][7][8][9][10][11][12][13][14][15][16] Diffusion-weighted imaging (DWI) and diffusion tensor imaging (DTI) are MR techniques sensitive to changes in the diffusion properties of water protons in terms of apparent diffusion coefficient (ADC), mean diffusivity (MD), or fractional anisotropy (FA). Previous studies using region of interest measurements have demonstrated that MD and FA in patients with LA are altered not only in the areas exhibiting signal intensity changes in T2-weighted images but also in the normal-appearing white matter.…”
mentioning
confidence: 99%